Estimation of Surface Energy Fluxes Using the Penman Monteith Method in a Tropical Station (2010)
The Penman Monteith (PM) model was applied in the estimation of sensible and latent heat fluxes on Nigerian Micrometeorological Experiment (Nimex_1) field at Obafemi Awolowo University, Ile-Ife, Nigeria, so as to validate its usage by comparing with direct eddy covariance measured fluxes. The resulting fluxes from the PM model were comparable to the measured eddy covariance ones. The root mean squared error (RMSE) ranging from 17.63 to 22.11Wm-2 and 38.72 to 76.08 Wm-2 was obtained for sensible and latent fluxes, respectively. The coefficient of determination for sensible and latent heat fluxes ranged from 0.83 to 0.90 and 0.78 to 0.90, respectively, with trend lines at the origin. The PM model gave a better estimation of sensible heat flux than the latent heat flux. The PM method was found to be rugged with respect to the choice of values for parameters of the correction advective term Fw which requires the inclusion of the relative humidity of the ground and the air near the surface. The resulting fluxes were not significantly dependent on the choice of the parameters, weather measured or assumed. The coefficient of determination between the two sets of computed fluxes were 1 for both sensible and latent heats. The RMSE ranged between 0.89 and 9.22 with the highest RMSE value on day of year (DOY) with the lowest soil moisture.